Integration of students with physical impairment in Canadian university rehabilitation sciences programs. - Guitard P; Duguay E; Thériault F; Sirois NJ; Lajoie M (International Journal of Rehabilitation Research, 2010)
The purpose of this research was two-fold. First, it sought to determine if Canadian rehabilitation science programs are equipped to admit students with physical impairments and, second, to document the experience of these students. A survey (questionnaire) conducted among all Canadian university rehabilitation science programs (n=34) and interviews with students with physical impairments (n=3) from one university help better delineate this problem. Twenty-three programs completed the survey. Of these, 21 (91%) rehabilitation science programs have admitted students with a variety of physical impairments. Programs have access to their university's Special Service Center to help answer the needs of these students. Strategies have been developed to overcome the difficulties encountered and to meet the programs' requirements. Canadian university rehabilitation science programs seem well equipped to facilitate the integration of individuals with physical impairments. Students report a positive university experience; however, they voice several recommendations to smooth the integration process. Although significant efforts have been made to facilitate the integration process of students with physical limitations, adjustments are still warranted.